The Anti-Viral and Anti-Inflammatory Properties of Edible Bird’s Nest in Influenza and Coronavirus Infections: From Pre-Clinical to Potential Clinical Application - Chua, Kien Hui; Mohamed, Isa Naina; Mohd Yunus, Mohd Heikal; Shafinaz Md Nor, Norefrina; Kamil, Khidhir; Ugusman, Azizah; Kumar, Jaya (Frontiers in Pharmacology, 2021)
Edible bird’s nest (BN) is a Chinese traditional medicine with innumerable health benefits, including anti-viral, anti-inflammatory, neuroprotective, and immunomodulatory effects. A small number of studies have reported the anti-viral effects of EBN against influenza infections using in vitro and in vivo models, highlighting the importance of sialic acid and thymol derivatives in their therapeutic effects. At present, studies have reported that EBN suppresses the replicated virus from exiting the host cells, reduces the viral replication, endosomal trafficking of the virus, intracellular viral autophagy process, secretion of pro-inflammatory cytokines, reorient the actin cytoskeleton of the infected cells, and increase the lysosomal degradation of viral materials. In other models of disease, EBN attenuates oxidative stress-induced cellular apoptosis, enhances proliferation and activation of B-cells and their antibody secretion. Given the sum of its therapeutic actions, EBN appears to be a candidate that is worth further exploring for its protective effects against diseases transmitted through air droplets. At present, anti-viral drugs are employed as the first-line defense against respiratory viral infections, unless vaccines are available for the specific pathogens. In patients with severe symptoms due to exacerbated cytokine secretion, anti-inflammatory agents are applied. Treatment efficacy varies across the patients, and in times of a pandemic like COVID-19, many of the drugs are still at the experimental stage. In this review, we present a comprehensive overview of anti-viral and anti-inflammatory effects of EBN, chemical constituents from various EBN preparation techniques, and drugs currently used to treat influenza and novel coronavirus infections. We also aim to review the pathogenesis of influenza A and coronavirus, and the potential of EBN in their clinical application. We also describe the current literature in human consumption of EBN, known allergenic or contaminant presence, and the focus of future direction on how these can be addressed to further improve EBN for potential clinical application.